Sorption of 4He, H2, Ne, N2, CH4, and Kr impurities in graphene oxide at low temperatures. Quantum effects - Dolbin, A.V.; Maser, W.K.; Bulakh, E.V.; Mysko, N.S.; Danchuk, V.V.; Basnukaeva, R.M.; Vinnikov, N.A.; Manzhelii, V.G.; Gavrilko, V.G.; Esel`son, V.B.; Benito, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Sorption and the subsequent desorption of 4He, H2, Ne, N2, CH4, and Kr gas impurities by graphene oxide(GO), glucose-reduced GO (RGO-Gl) and hydrazine-reduced GO (RGO-Hz) powders have been investigated in the temperature interval 2–290 K. It has been found that the sorptive capacity of the reduced sample RGO-Hz is three to six times higher than that of GO. The reduction of GO with glucose has only a slight effect on its sorptive properties. The temperature dependences of the diffusion coefficients of the GO, RGO-Gl and RGO-Hz samples have been obtained using the measured characteristic times of sorption. It is assumed that the temperature dependences of the diffusion coefficients are determined by the competition of the thermally activated and tunneling mechanisms, the tunneling contribution being dominant at low temperatures.